E-CATALOG APPLICATION FOR FOOD AND BEVERAGES AT RUANG SEDUH CAFÉ BASED ON AUGMENTED REALITY - Andi Nurkholis; Dyah Ayu Megawaty; M Fabian Apriando (Jurnal Teknoinfo, 2022)
Café is a place where people gather while enjoying the dishes provided, such as drinks and food accompanied by music and comfortable facilities and infrastructure. The dishes listed in the café menu book vary with various and unfamiliar names. Sometimes the variety of dishes served does not match expectations, leading to customer dissatisfaction, thus allowing customers to be reluctant to come back. This study proposes an innovation on service quality by developing an Android-based e-catalog application for dish dishes. The application of Augmented Reality on the display of the food or beverage menu is used to beautify the aesthetics of the dish and attract customers to come back. The system was developed using a prototype method applied to an Android-based application using the Kotlin programming language, MySQL as a database, and testing using ISO 25010. Through this AR-based food and beverage e-catalog application, customers can view information on the café's dishes, which are categorized by best-selling menu, latest menu, and all menus. Customers can also view the presentation in a 3D image and its rating. Based on the results of testing on 50 respondents, it was found that this AR-based food and beverage e-catalog application resulted in a usability test of 96% and a functional suitability test of 100%. So it can be concluded that the percentage value obtained shows the overall software quality has a "Very Good" scale and is feasible to use.